Cross-Cultural Technology Adaptation in Global Video Consultation Platforms: Language, Interface Design, and Cultural User Experience - Septien Dwi Savandha (Publikasi Indonesia, 2025)
The globalization of video consultation platforms has exposed critical gaps in cross-cultural technology adaptation, with linguistic and cultural barriers significantly impeding equitable access to healthcare. This study investigated how cultural and linguistic factors influence user experience with video consultation platforms across diverse global contexts. A qualitative phenomenological approach was employed, utilizing purposive sampling to recruit 45 participants from six countries (Indonesia, Japan, Lebanon, India, Germany, Brazil) representing distinct cultural dimensions. Data collection occurred through semi-structured interviews (45-60 minutes) and think-aloud protocol sessions (n=18) between March and September 2024. Reflexive thematic analysis, following Braun and Clarke's framework, was conducted, achieving intercoder reliability (κ = 0.87), with data saturation confirmed at 38 participants. Five primary themes emerged: linguistic accessibility barriers affected 82.2% of non-English-speaking participants, and medical terminology translation difficulties ranged from 57.1% to 87.5% across countries. Collectivist culture participants (82.6%) preferred family-inclusive features, whereas individualist culture participants (80%) preferred individual-focused interfaces. Participants from a high-context communication culture required 47% longer to complete the task. Privacy priorities varied substantially, reflecting cultural specificity in trust-formation mechanisms. Visual design preferences varied markedly in color symbolism, information density (42%-78% preferred screen coverage), and icon recognition rates (37.5%-87.5%). Cultural and linguistic factors fundamentally shape the usability of video consultation platforms across multiple dimensions. Findings challenge universal design paradigms, establishing cultural responsiveness as essential to the equitable deployment of telemedicine. Platform developers must integrate comprehensive cultural adaptation, encompassing linguistic localization, accommodation of communication patterns, culturally appropriate privacy frameworks, and customization of visual design.